2021
DOI: 10.3390/f12081069
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Projection of Species-Specific Responses to Chronic Additions of Nitrogen, Sulfur, and Lime

Abstract: Elevated acid deposition has been a concern in the central Appalachian region for decades. A long-term acidification experiment on the Fernow Experimental Forest in central West Virginia was initiated in 1996 and continues to this day. Ammonium sulfate was used to simulate elevated acid deposition. A concurrent lime treatment with an ammonium sulfate treatment was also implemented to assess the ameliorative effects of base cations to offset acidification. We show that the forest vegetation simulator growth mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Similar studies related to the N cycle have been conducted, mainly in coniferous forest ecosystems, since the 1970s [7][8][9][10][11]. In addition, the N biogeochemical research has been ongoing for 30 years at another North American temperate forest site (Fernow Experimental Forest) [12][13][14][15][16][17][18][19][20][21]. They have reported that soil N pools comprise a major proportion of the total N pools.…”
Section: Introductionmentioning
confidence: 82%
“…Similar studies related to the N cycle have been conducted, mainly in coniferous forest ecosystems, since the 1970s [7][8][9][10][11]. In addition, the N biogeochemical research has been ongoing for 30 years at another North American temperate forest site (Fernow Experimental Forest) [12][13][14][15][16][17][18][19][20][21]. They have reported that soil N pools comprise a major proportion of the total N pools.…”
Section: Introductionmentioning
confidence: 82%
“…Not surprisingly, the response of forest trees to excess N can be highly species specific, and work at FEF has shown that several hardwood species, such as sweet birch (Betula lenta L.), black cherry (Prunus serotina Ehrh. ), and red maple (Acer rubrum L.) responded positively to N additions, whereas yellow poplar (Liriodendron tulipifera L.) responded negatively [16]. These species-specific responses have implications for ecosystem-level effects of N on forests, as some hardwood species, especially sugar maple (Acer saccharum L.), can facilitate greater loss of N, via leaching of NO 3 − , by enhancing rates of net nitrification [17].…”
mentioning
confidence: 99%